The Effect of Saffron Kozanis (Crocus sativus L.) Supplementation on Weight Management, Glycemic Markers and Lipid Profile in Adolescents with Obesity: A Double-Blinded Randomized Placebo-Controlled Trial - Eleni P. Kotanidou; Vasiliki Rengina Tsinopoulou; Styliani Giza; Stergianna Ntouma; Chrysanthi Angeli; Michail Chatziandreou; Konstantinos Tsopelas; Ioulia Tseti; Assimina Galli-Tsinopoulou (MDPI AG, 2023)
Global rates of adolescent obesity have led the World Health Organization to consider the disease a pandemic that needs focus. In search of new anti-obesity agents, Crocus sativus, popularly known as saffron, is a nutraceutical agent, praised for its beneficial effects. The study aimed to investigate the possible effect of Kozanis saffron administration on weight management of obese prediabetic adolescents. Seventy-four obese prediabetic adolescents participated in a double-blind placebo-controlled trial of three arms, randomly assigned to receive either Kozanis saffron (n = 25, 60 mg/day), metformin (n = 25, 1000 mg/day) or a placebo (n = 24), for twelve weeks. Anthropometry, glycemic markers and lipid profiles were investigated at baseline and post-intervention. Saffron supplementation significantly reduced the weight z-score, BMI, BMI z-score and waist circumference (WC) of obese adolescents; however, this reduction was less significant compared to the effect of metformin. Metformin administration offered a significantly more profound improvement in anthropometry compared to saffron administration. Saffron administration also provided significant improvements in weight, weight z-scores, BMI values, BMI z-scores and WCs compared to the placebo. Saffron supplementation failed to change any glycemic marker, but provided a significant reduction in fasting triglyceride levels and also a significant increase in fasting HDL levels. Saffron Kozanis constitutes a promising nutraceutical option for adolescents and children with obesity and prediabetes in need of weight management.